2013
DOI: 10.4028/www.scientific.net/kem.543.89
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Potential <i>In Vivo</i> Genotoxicity of Tungsten (VI) Oxide Nanopowder for Human Health

Abstract: Tungsten (VI) oxide particles (WO3, <100 nm particle size) are used for many purposes including production of electro chromic windows, or smart windows, x-ray screen phosphors and gas sensors in everyday life. However, the carcinogenic and genotoxic potential of this nanomaterial have not been sufficiently evaluated. Therefore, the genotoxic potential of WO3was examined in Sprague-Dawley rat bone marrow cells by using mitotic index (MI), micronucleus (MN) and chromosome aberrations (CA) assays. Rats were or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 14 publications
2
14
1
Order By: Relevance
“…In contrast to our in vitro findings, WO 3 NPs showed positive mutagenic response in TA1537 and TA98 bacterial strains of Salmonella typhimurium by using Ames test (Hasegawa et al 2012). WO 3 NPs did not cause increase of the incidence of chromosome aberrations in rat bone marrow cells but led to increases of MN formation after chronic exposure for 30 days (Turkez et al 2013a). These conflicting evidences on genotoxicity by WO 3 NPs could be explained by the differences in conditions (in vivo or in vitro), exposuring time (acute, chronic or sub chronic) and chemical features of tested NPs (exact size, shape, composition, and aggregation).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In contrast to our in vitro findings, WO 3 NPs showed positive mutagenic response in TA1537 and TA98 bacterial strains of Salmonella typhimurium by using Ames test (Hasegawa et al 2012). WO 3 NPs did not cause increase of the incidence of chromosome aberrations in rat bone marrow cells but led to increases of MN formation after chronic exposure for 30 days (Turkez et al 2013a). These conflicting evidences on genotoxicity by WO 3 NPs could be explained by the differences in conditions (in vivo or in vitro), exposuring time (acute, chronic or sub chronic) and chemical features of tested NPs (exact size, shape, composition, and aggregation).…”
Section: Discussioncontrasting
confidence: 55%
“…With frequent exposure to dispersed nanoparticles from the composite products or workplaces, there is an increased chance for nanoparticles or nano composites to enter human body and to relocate in metabolism-active organs (Song et al 2009). Thus, studying the toxicity of nanomaterials is of importance to provide the guidance to occupational health and safety (Li et al 2008;Lanone et al 2009;Turkez et al 2013a). The discussion about safety concerns associated with small particles is ongoing for many decades and, to a large extent, is related to the potential risks following inhalative, oral, parenteral or dermal exposure ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that higher dose exposure to nanomaterials, including silica, titanium dioxide, tungsten oxide, zinc oxide and alumina NPs led to proinflammatory and procoagulant responses in endothelial cells (Liu and Sun, 2010;Oesterling et al, 2008;Schanen et al 2009;Sha et al, 2013;Turkez, 2008, Turkez et al, 2013b. It is an accepted viewpoint that ROS are involved in many of the processes underlying endothelial activation (e.g., the upregulation of adhesion molecules and chemokines, increased expression of tissue factor).…”
Section: Discussionmentioning
confidence: 99%
“…From neutron shielding point of view, tungsten has some desirable properties. Besides unique chemical, physical and mechanical properties (Speers, 2011), it does not have the toxicity of lead (Turkez et al, 2013) and have a decent thermal neutron cross-section (~18 barns) in comparison with lead (~ 0.17 barns) (Lide, 2011). So, tungsten could serve a dual purpose of shielding against gamma rays and neutrons.…”
Section: -Introductionmentioning
confidence: 99%